2018
DOI: 10.1159/000492948
|View full text |Cite
|
Sign up to set email alerts
|

Subretinal Fluid Optical Density and Spectral-Domain Optical Coherence Tomography Characteristics for the Diagnosis of Circumscribed Choroidal Hemangioma

Abstract: Purpose: To investigate spectral domain-optical coherence tomography (SD-OCT) features of untreated circumscribed choroidal hemangioma (CCH), and the optical density (OD) of the associated subretinal fluid (SRF). Procedures: This international retrospective multicenter study conducted at 5 tertiary retina referral centers included 34 patients with symptomatic CCH imaged on SD-OCT. CCH surface, size, and overlying retinal changes and OD ratio (ODR) were evaluated. Results: The mean ODR of the SRF was 0.808 ± 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Our results are consistent with the observations by Leshno et al 9 and Zur et al 9 , 10 regarding the higher ODR of SRF in choroidal melanoma than in other benign or malignant choroidal lesions. Our findings demonstrate that choroidal melanoma have also higher SRF ODR than choroidal naevus.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Our results are consistent with the observations by Leshno et al 9 and Zur et al 9 , 10 regarding the higher ODR of SRF in choroidal melanoma than in other benign or malignant choroidal lesions. Our findings demonstrate that choroidal melanoma have also higher SRF ODR than choroidal naevus.…”
Section: Discussionsupporting
confidence: 94%
“…They computed using a receiver operating characteristic (ROC)-curve approach with a cutoff value of 0.771 with sensitivity of 78.6% and specificity of 72.0%. Another study by the same group by Zur et al 10 also identified a higher SRF ODR in 25 cases with choroidal melanoma, compared with 34 cases with circumscribed choroidal hemangioma.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…We wonder if these kinds of lesions could be hemangiomas. In fact, on optical coherence tomography, hemangioma is characterized by: 9,10 Localized choroidal mass with large inherent vasculature, without choroidal vessels compression.Subretinal fluid and cystic retinal degeneration may be present above the tumor.Tumor mass exhibits a hyporeflective internal signal.…”
mentioning
confidence: 99%